Emotion management in the workplace - Bolton, Sharon C. (Palgrave Macmillan, 2005)
The work explores the management of emotion in organizations and the emotion management skills organizational actors need to possess in order to achieve organizational objectives while also acknowledging the subjective experiences of its members. The key strength of this text lies in its critical approach and labor-process orientation. It will appeal to students of organizational studies, gender studies, sociology and human resource management at the undergraduate and postgraduate levels.